Multiple language exposure for children with autism spectrum disorder from culturally and linguistically diverse communities. Issue 3 (2nd July 2020) - Conner, Carlin; Baker, Doris L.; Allor, Jill H.
ABSTRACT: We review studies that examined whether children who have been diagnosed with autism spectrum disorder (ASD) and who are from culturally and linguistically diverse communities benefit more from being exposed to one versus two or more languages. Fourteen articles fit our criteria. The findings suggest that children with ASD benefit from richer interactions with parents and teachers in their native language. These findings are inconsistent with current practitioner recommendations that advise parents of children with ASD to speak only the majority language to reduce the deficit in language development associated with ASD. In fact, the results from the review suggest that there appears to be no advantages to limiting a child with ASD to one language. Some studies indicate that promoting the use of the child's native language along with the predominant language used at school may actually promote social language and academic growth.